2015
DOI: 10.9734/bjesbs/2015/14819
|View full text |Cite
|
Sign up to set email alerts
|

Computational Chemistry Programs as a Facilitating Tool in the Teaching and learning Process

Abstract: Aims:To verify the influence of the role of ICT's (Information and Communication Technologies) as a teaching and learning process in the classes of chemistry discipline for the 3 rd years high school students, and show the importance of computational chemistry programs as a methodological alternative in the comprehension of chemical concepts of macroscopic and microscopic order. Place and Duration of Study:The research was carried out in a public high school in the city of Macapá-AP, Brazil. Study Design: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In addition, training chemistry teachers to use and implement CC software in their teaching significantly contributed to their contemporary content knowledge in chemistry, which was reflected in their motivation to integrate these tools in class (Traube and Blonder, 2023). Regarding the benefits of using CC methods, there is not much evidence of their use, and the available evidence mainly refers to undergraduate students (Silva et al, 2015;Esselman and Hill, 2016;Snyder and Kucukkal, 2021). This uncommon implementation could be due to infrastructure issues (e.g., software prices, maintenance, and technical support), the need for technical training, students' limited theoretical background regarding the calculations, lecturers' TPASK (technological, pedagogical, and scientific knowledge) that is not fully developed, and their self-efficacy, especially when CC is not their area of expertise (Tuvi-Arad, 2022).…”
Section: Using Computational Methodsmentioning
confidence: 99%
“…In addition, training chemistry teachers to use and implement CC software in their teaching significantly contributed to their contemporary content knowledge in chemistry, which was reflected in their motivation to integrate these tools in class (Traube and Blonder, 2023). Regarding the benefits of using CC methods, there is not much evidence of their use, and the available evidence mainly refers to undergraduate students (Silva et al, 2015;Esselman and Hill, 2016;Snyder and Kucukkal, 2021). This uncommon implementation could be due to infrastructure issues (e.g., software prices, maintenance, and technical support), the need for technical training, students' limited theoretical background regarding the calculations, lecturers' TPASK (technological, pedagogical, and scientific knowledge) that is not fully developed, and their self-efficacy, especially when CC is not their area of expertise (Tuvi-Arad, 2022).…”
Section: Using Computational Methodsmentioning
confidence: 99%
“…The study conducted by (Pyatt, 2014 ) showed that computer software is important to teach and assess the writing of chemical reactions and balancing chemical reactions, and writing types of chemical reactions. The use of Chemsketch and PhET computer software increases student’s conceptual understanding of the representation of the chemical structure of ozone, water, carbon dioxide, and methane molecules, it was also found that PhET software is effective in teaching polarity of molecules, electronegativity, molecular geometry, physical and chemical properties of the molecules (Silva et al, 2015 ; Julboev et al, 2021 ) found that computer software such as ChemDraw, Isis/Draw, ChemBio-Draw, HyperChem, Gaussian, Chemofis, and Crocodile Chemistry creates the basis for increasing students’ interest in Chemistry, transferring and consolidating knowledge. With the increase of technologies, web 2 Web 2.0?…”
Section: Web-based Learning Is the Construction Of Knowledge In Chemi...mentioning
confidence: 99%
“…Many internet-based computational programs and software are widely available and can be freely accessed to support chemistry teaching and learning such as PyMOL and Jmol (Craig et al, 2013). Visualization programs and/ or computational chemistry simulation software such as ChemSketch and PhET have also been used as learning methodologies that are reported to be able to reduce student learning difficulties (Silva et al, 2015). ChemDraw and HyperChem are two popular computational chemistry software products that have been widely utilized by the educational community both in high schools and universities.…”
Section: Introductionmentioning
confidence: 99%